Pico’s Kabbalistic Exegesis in Heptaplus: An Outline of the Problem - Herůfek, Jan (Verbum – Analecta Neolatina, 2024)
The paper deals with Giovanni Pico della Mirandola’s concept of kabbalistic exegesis. This is mostly apparent in his works Commento (1486), Conclusiones (1486), Apologia (1487) and Heptaplus (1489). Firstly, the study focuses on the origins and motifs of Pico’s kabbalistic exegesis in the framework of prisca theologia. Secondly, it analyses potential Jewish sources (e.g., “Abulafia”, “Recanati”), translated by Flavius Mithridates, and then considers, how Pico incorporates those into his kabbalistic exegesis in Heptaplus in particular. In this context, it must be said that due to Mithridates, Pico’s concept of Kabbalah acquires an almost supernatural and divine character.